SISTEM PERJODOHAN PADA PERNIKAHAN DI BAWAH UMUR PERSPEKTIF HUKUM POSITIF DAN MAQASHID SYARIAH - Ramadhani, Suci; Lilik Andaryuni; Akhmad Sofyan (AR-RA'YU : Jurnal Hukum Keluarga Islam, 2023)
This Research explores the persistence of underage marriage through matchmaking traditions in Mattoanging, Soppeng Regency. Despite Law No. 16 of 2019—which amended Law No. 1 of 1974 and raised the minimum marriage age to 19—arranged underage marriages remain practiced, reflecting tension between local customs, Indonesian positive law, and the objectives of sharia (maqashid syariah).Using a qualitative, normative-empirical approach, the study collected primary data from minors married through matchmaking, their parents, and religious leaders, supported by books, journals, and documents.Findings reveal three types of matchmaking systems: mammu’-manu’ (bird-hunting custom), ancestral traditions, and childhood arrangements. Five factors sustain these practices: cultural adherence, economic motives, parental concerns, educational barriers, and kinship ties.From a legal perspective, underage matchmaking conflicts with Article 28B(1) of the 1945 Constitution, Law No. 39 of 1999 on Human Rights Article 10(1), and Law No. 16 of 2019 Article 7(1). These emphasize children’s rights to choose their partners and aim to curb underage marriages.Through the lens of maqashid syariah, such practices threaten essential protections (dharuriyat): (1) Hifdz ad-Din—religious obligations may be neglected; (2) Hifdz an-Nafs—mental and physical immaturity risks health; (3) Hifdz al-‘Aql—intellectual development is disrupted; (4) Hifdz an-Nasl—early pregnancy endangers reproduction; and (5) Hifdz al-Mal—economic unpreparedness threatens household stability.Thus, underage arranged marriages in Mattoanging are not only inconsistent with state law but also contradict maqashid syariah, necessitating legal-social harmonization.